Description Of Hepatitis Infection With Differential Leukocyte Count In Mataram City Hospital - Urip, Urip; Sitiana, Nining; Pauzi, Iswari; Jiwantarum, Yunan (Jurnal Analis Medika Biosains (JAMBS), 2025)
Hepatitis is an infectious disease characterized by increased levels of liver enzymes due to damage or disruption of the liver membrane. Hepatitis consists of various viruses. Hepatitis A is caused by infection with the hepatitis A virus (HAV), hepatitis B is caused by infection with the hepatitis B virus (HBV), hepatitis D is caused by infection with the hepatitis D virus (HDV), and hepatitis E is caused by infection with the hepatitis E virus (HEV). The objectives of this research are to find out the relationship between the type of Hepatitis infection and the Differential Count of leukocytes in the Mataram City Regional Hospital. The method of this research is Observational Analytical. The sampling technique in this research is the Purposive Sampling technique. The sample used in this research is the serum of Hepatitis sufferers. The population in this study is medical record data of hepatitis sufferers who underwent leukocyte type examination from January-December 2022 in Mataram City Regional Hospital, The number of samples obtained was 59 samples with types of Hepatitis A, B, and C. Data analysis used descriptive frequency. The results of this research were that the average results for the type of leukocyte Hepatitis B (HBV) mean basophils were 0.15%, eosinophils 1.89%, 75.72% neutrophils, 16.24% lymphocytes, and 6.02% monocytes. C (HCV) means basophils 0%, eosinophils 1.5%, neutrophils 82%, lymphocytes 10%, and monocytes 6%. This research concludes that there is an increase in neutrophils and a decrease in lymphocytes.